Development and characterization of magnetic polyethyleneimine-bamboo nanocellulose adsorbents for enhanced performance of dye pollutant removal - Jameelah Alhadi Salih Othman; Norzita Ngadi; R. A. Ilyas; Abu Hassan Nordin; M. F. M. Alkbir; Mohd Nor Faiz Norrrahim; Victor Feizal Knight; Khalid A. Alzahrani; Anish Khan; Pijush K. Mondal (Bioresources and Bioprocessing)
Abstract The adsorption of reactive black 5 (RB5) onto bamboo nanocellulose modified with polyethyleneimine (PEI) and magnetic nanoparticles (MNPs), referred to as MNCPEI (Fe3O4, ~ 10–20 nm), were incorporated via direct dispersion during the synthesis process without surface pre-functionalization was systematically examined in aqueous solution. The efficiency of dye removal increased proportionally with the amount of MNCPEI in the modified adsorbents. Characterization studies revealed that the MNCPEI modification significantly enhanced the surface chemistry of the adsorbents while providing slight improvements in their textural properties. High removal efficiencies for the anionic dyes were consistently achieved, demonstrating the superior performance of the MNCPEI adsorbents. Optimal adsorption conditions were observed at a nanocellulose-to-PEI ratio of 1:2 and an MNP dosage of 0.3 g. The findings indicated that the adsorption of RB5 was governed by monolayer adsorption, with chemical adsorption identified as the rate-limiting step. The adsorbent exhibited a high maximum adsorption capacity (99%) for RB5, attributed to the increased availability of functional groups facilitating interaction with the dye molecules. Key parameters affecting the adsorption process, including contact time (0–180 min), adsorbent dosage (0.05–2.0 g), initial dye concentration (0.025–0.3 g/L), pH (2–9), and temperature (25–70 °C), were investigated. This study underscores the potential of bamboo-derived MNCPEI adsorbents for effective textile wastewater treatment. Graphic Abstract